The Use of Inverters in Solar Power Plants for Alternating Current Loads - Noorly Evalina; Faisal Irsan Pasaribu; Abdul Azis H (Britain International for Academic Research (BIAR) Publisher, 2021)
The sun shines on the territory of Indonesia for about 10 to 12 hours every day, so that solar power plants can be developed in Indonesia, the government has launched the movement of one million PLTS roofs in 2017, this research uses solar panels with a capacity of 200 Wp, which consists of 2 solar panels connected in parallel, solar charge controllers, batteries, inverters and as an AC load a fan, soldering iron and LED lights, the research aims to determine the output current, voltage and output power of the inverter when given an alternating current load that is inductive, resistive and capacitive, the method used is to measure the intensity of the sun, temperature, voltage, electric current, power factor, when the load is large the voltage drops depending on the given load, the inductive fan load has a voltage drop that is greater than the voltage drop that occurs in the soldering load and the LED lamp, the large current flowing on the output side fan load wants to be bigger than output current flowing in the solder and LED lights, the low efficiency of the inverter used can shorten the life of the electrical equipment used.